Q Fever During Pregnancy: An Emerging Cause of Prematurity and Abortion - Francisco Jover-Díaz; Jaqueline Robert-Gates; Lucio Andreu-Gimenez; Jaime Merino-Sanchez (Hindawi Limited, 2001)
Background: Although the pathogenic role of Coxiella burnetii infection during pregnancy is controversial, some cases of stillbirth and abortion occurring after an acute or chronic infection have been mentioned in the literature. Recently, Q fever has been advocated as a significant cause of morbidity and mortality in pregnancy